The Effect of a Portable Electrical Muscle Stimulation on Brain-Derived Neurotrophic Factor in Elderly People: Three Case Studies - Yuichi Nishikawa PhD; Kohei Watanabe PhD; Shuhei Kawade BSC; Noriaki Maeda PhD; Hirofumi Maruyama PhD (Gerontology and Geriatric Medicine, 2021)
Brain-derived neurotrophic factor (BDNF), which plays an important role in cognitive and nerve function, is released from skeletal muscle cells into the blood by muscle contractions and/or electrical muscle stimulation (EMS). However, the influence of EMS administered by a portable device on BDNF is unclear. The purpose of this case report was to quantify the influence of EMS administered by a portable device on BDNF and physical function. Three elderly people (age, 69.7 ± 1.5 years) were included in the present study. The participants used a portable EMS device to stimulate the bilateral quadriceps muscles for 8 weeks (23 min for 5 days/week). To determine the effects of EMS, the following parameters were assessed at baseline, 8 weeks, and 12 weeks (follow-up): knee extensor strength, muscle mass of the lower limb, Berg balance score, and blood BDNF level. All outcomes improved after the EMS intervention, but the improvements did not persist for 12 weeks. These findings suggest that portable EMS is potentially useful for improving the blood BDNF level and physical function.